Embracing Ebooks : Acquisition and Collection Development Landscape in Philippine Academic Libraries - Janice D.C. Peñaflor; Justina Garcia (Jiàoyù zīliào yǔ túshūguǎn xué, 2017)
In the recent years, libraries are evidently expanding their embrace in adoption of ebooks. This may be attributed to the real and perceived advantages demonstrated by ebooks in terms of accessibility, functionality and cost effectiveness. Increasingly, ebooks form a growing part of the collections in academic libraries as a viable format to support the information needs of their patrons. Some libraries have adopted ebooks on a large scale while others are still tentative in their acquisitions. This study aims to examine the current status of collection build-up of ebooks in different academic libraries in Metro Manila. Specifically, it will look at the extent by which they collect and acquire ebooks as well as the issues being faced by the libraries in their efforts to build their ebook collection. This paper employs a survey method to determine the collection size, selection models, methods of acquisition, budget allocation, collection development policy and other related items. The results of the study will provide an overview of the extent of ebook adoption among the academic libraries in the Philippines. It will also serve as a basis for proposing possible solutions to common issues that confronts the libraries of today concerning integrating ebooks in the collection. Lastly, the findings may also serve as a benchmark for best practices for other libraries.